Pushover Analysis of Steel Seismic Resistant Frames with Reduced Web Section and Reduced Beam Section Connections - Naughton, Daniel Tomas; Tsavdaridis, Konstantinos Daniel; Maraveas, Chrysanthos; Nicolaou, Andreas (Frontiers in Built Environment, 2017)
The widespread brittle failure of welded beam-to-column connections caused by the 1994 Northridge and 1995 Kobe earthquakes highlighted the need for retrofitting measures effective in providing ductility to connections. Researchers presented the reduced beam section (RBS) as a viable option to prevent brittle failure at the connection weld. More recently, an alternative connection known as a reduced web section (RWS) has been developed as a potential replacement, and initial studies show ideal performance in terms of rotational capacity and ductility. This study performs a series of non-linear static pushover analyses using a modal load case on three steel moment-resisting frames (MRFs) of 4-storeys, 8-storeys and 16-storeys. The frames are studied with three different types of connections; fully-fixed moment connections, RBS connections and RWS connections, in order to compare the differences in capacity curves, inter-storey drifts and plastic hinge formation. The seismic-resistant connections have been modelled as non-linear hinges in ETABS, and their behaviour have been defined by moment-rotation curves presented in previous recent research studies. The frames are displacement controlled to the maximum displacement anticipated in a 2 in 50 earthquake. The study concludes that RWS connections perform satisfactorily when compared with frames with fully-fixed moment connections in terms of providing consistent inter-storey drifts in low to mid-rise frames, without significantly compromising the overall strength capacity of the frames. The use of RWSs in taller frames causes an increase in inter-storey drifts in the lower storeys, as well as causing a large reduction in strength capacity. Frames with RWS connections behave comparably to frames with RBS connections and are deemed a suitable replacement.